Odpowiedź:
d)
5x-7-x=9-2-4
4x= 3 + 7
4x= 10 /:4
x= 10:4
x= 2,5
e)
6-8-x= 9-2x-3
-2-x=9-2x-3
2x-x=9-3+2
x= 8
f)
5x-1+6x=32
11x= 32+1
11x= 33 /: 11
x= 33:11
x=3
g)
11x-6= 7-4
11x=3+6
11x=9 /:11
x= 9:11
x= 9/11
h)
4x+ 3= 9-12
4x= 3-3
4x=0 /:4
x=0 /nie dzieli się wogóle nic przez 0
1)
6x+5x+4= 6+5x+4
11x-5x= 6+4-4
6x=6 /:6
x= 6:6
x=1
1)
4-5x-6x=6-5-4x
-x+4x= 6-5-4
3x= 5 /:3
x= 5:3
x= 5/3
x= 1 i 2/3
k)
x+10x+100= 1+10x +100
11x-10x= 1+100-100
x=1
1)
10*20+30-10-20-x+30= 200+30-10-20-x+30
230-10-20-x+30= 220-20-x+30= 200-x-20-x+30= 200-x
Szczegółowe wyjaśnienie:
z ostatnim nic więcej nie mogłam zrobić i co do g to chyba coś źle napisałaś/eś albo o to chodzi